Human resource development strategy in empowering the employees - Waelan, Waelan; Santra, I Ketut; Wijayati, Luh Made; Kasiani, Kasiani; Asrumi, Asrumi (YAYASAN MITRA PERSADA NUSANTARA, 2023)
Implementing human resource development strategy in empowering senior and junior employees for the training of the labor force in order improve discipline, work attitude and work ethic in order to achieve more than theory. The aim of this research is to know how the company execute the strategies for implementing strategy management theories. Several obstacles have been found that they can influence the performance of job training. So, it takes research back to minimize existing problems through. The assessment indicator used in this study is 4 (four) strategic management phases with the following indicators 1) environmental analysis, 2) formulation of strategies, 3) implementation of strategy and 4) evaluation and control. The humanitarian approach in developing human resources is more effective than the theoretical approach. In other words, the theoretical approach plus the humanitarian approach is harmoniously applied